The effects of whey protein and chromium picolinate supplementation on visceral fat and metabolic status in high-fat-fed rats - Şahin, Kazım; Juturu, Vijaya; Tuzcu, Mehmet; Şahin, Nurhan; Cikim, Gurkan; Komorowski, James R. (Ios Press, 2009)
The objective of this study was to evaluate the effects of whey protein (WP) and chromium picolinate (CrPic) on body composition and metabolic status in rats fed a high-fat diet (HFD). Male Wistar rats (n = 10/group, 8 weeks old) were divided into three groups. The control group was fed a HFD (300 g fat/kg diet). The other two groups were fed the HFD plus 320 g whey protein isolate/kg diet (HFD + WP) with or without 80 mcg CrPic/kg body wt/day (HFD + WP + CrPic). After six weeks, rats were fasted, blood samples were drawn, and visceral and subcutaneous fat pads were removed and weighed. Daily food intake was not affected by treatment. Rats fed HFD exhibited significant increases in body weight, body fat and metabolic risk factors (p <= 0.05). Rats fed the HFD + WP showed a significant decrease in body weight, serum glucose and blood lipids, and a significant increase in insulin levels (p <= 0.05). Rats fed the HFD + WP + CrPic had the lowest levels in total visceral fat, triglycerides, total cholesterol and free fatty acids, and the highest insulin levels (p <= 0.05). Tissue concentrations of chromium (Cr) increased with CrPic supplementation (p < 0.001). The results of this study support the use of WP and CrPic supplementation to improve body composition and metabolic syndrome risk factors.
Keywords: Chromium; Whey protein; Insulin resistance; Metabolic syndrome